Evaluation of a wireless activity monitoring system to quantify locomotor activity in horses in experimental settings. (22nd March 2016) - Fries, M.; Montavon, S.; Spadavecchia, C.; Levionnois, O. L.
Summary: Reasons for performing study: Methods of evaluating locomotor activity can be useful in efforts to quantify behavioural activity in horses objectively. Objectives: To evaluate whether an accelerometric device would be adequate to quantify locomotor activity and step frequency in horses, and to distinguish between different levels of activity and different gaits. Study design: Observational study in an experimental setting. Methods: Dual‐mode (activity and step count) piezo–electric accelerometric devices were placed at each of 4 locations (head, withers, forelimb and hindlimb) in each of 6 horses performing different controlled activities including grazing, walking at different speeds, trotting and cantering. Both the activity count and step count were recorded and compared by the various activities. Statistical analyses included analysis of variance for repeated measures, receiver operating characteristic curves, Bland–Altman analysis and linear regression. Results: The accelerometric device was able to quantify locomotor activity at each of the 4 locations investigated and to distinguish between gaits and speeds. The activity count recorded by the accelerometer placed on the hindlimb was the most accurate, displaying a clear discrimination between the different levels of activity and a linear correlation to speed. The accelerometer placed on the head was the only one to distinguish specifically grazing behaviour from standing. The accelerometer placed on the withers was unable to differentiate different gaits and activity levels. The step count function measured at the hindlimb was reliable but the count was doubled at the walk. Conclusions: The dual‐mode accelerometric device was sufficiently accurate to quantify and compare locomotor activity in horses moving at different speeds and gaits. Positioning the device on the hindlimb allowed for the most accurate results. The step count function can be useful but must be manually corrected, especially at the walk.